Sunlight exposure, antioxidant status, and cataract in Hong Kong fishermen. Issue 1 (February 1993) - Wong, L; Ho, S C; Coggon, D; Cruddas, A M; Hwang, C H; Ho, C P; Robertshaw, A M; MacDonald, D M
Abstract : STUDY OBJECTIVES–The aim was to test whether cataract is associated with higher lifetime exposure to sunlight, and whether antioxidants protect against cataract. DESIGN–This was a cross sectional survey of eye disease, with assessment of antioxidant status in a subgroup. SETTING–Hong Kong fishing communities in 1989. PARTICIPANTS–685 men and women aged 55 to 74 years old were included in the study, of whom 367 (54%) attended hospital for detailed examination. MEASUREMENTS AND MAIN RESULTS–At a mobile clinic visual acuity and lens opacities were assessed, and using a questionnaire, occupational history and lifetime exposure to sunlight. At hospital ophthalmic measurements were repeated and blood was taken for measurement of plasma vitamin C, vitamin E, and total carotenoids, and red cell activities of glucose-6-phosphate dehydrogenase, glutathione peroxidase, superoxide dismutase, and catalase. Higher grades of cataract (particularly nuclear cataract) tended to be more common in subjects with the most sun exposure, although not to the point of statistical significance. In contrast to earlier studies, no association was found with antioxidant status. CONCLUSIONS–The findings give some support to the hypothesis that sunlight causes cataract. The absence of a relation to antioxidant status may be because blood levels of antioxidants at one point in time do not adequately reflect a subject's past metabolic state, and particularly the past activity of antioxidants in the lens.